Performance analysis of an optimal resource allocation method for the water-filled channel of the OFDMA cellular network to support multimedia traffic. (21st October 2009) - Kumar, Dhananjay; Chellappan, C.
The multimedia traffics are bursty and require high dynamic bandwidth support to meet its quality of service (QoS). The orthogonal frequency division multiple access (OFDMA) technique can support this diverse requirement, while enhancing the system capacity and resource management. An optimal resource allocation method called two-stage rate adaptive (TSRA) algorithm is proposed here. The TSRA employs an adaptive modulation techniques and a bandwidth adaptation (BWA) algorithm to support the dynamic resource requirement of a multimedia traffic. The BWA is invoked dynamically by TSRA to deal with real-time variable bit rate services. A water-filling of subchannel is carried out before applying TSRA to further optimise the system capacity. It is observed that the TSRA with water-filled subcarriers follows closely the analytical/theoretical limit for increasing number of users. The throughput per OFDMA symbol observed here can serve a large variety of multimedia services. We also simulate the delay performance of the TSRA for the existing and the new arrival of multimedia traffic.